2020
DOI: 10.5194/nhess-2020-361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The prediction of floods in Venice: methods, models and uncertainty

Abstract: Abstract. This paper reviews the state-of-the-art in storm surge forecasting and its particular application in the northern Adriatic Sea. The city of Venice relies crucially on a good flood forecasting system in order to protect the extensive cultural heritage, their population, and their economic activities. Storm surge forecasting systems are in place to warn the population of imminent flood threats. In the future, it will be of paramount importance to increase the reliability of these forecasting systems, e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…In Italy, the increasing frequency of coastal floods has been driven by an average sea level rise of 47 cm over the past 150 years [101], and sinking of the coast by natural and anthropogenic subsidence [102]. In Venice, the Italian coastal city most prone to flooding, the impacts of sea level rise are managed by mobile infrastructure called MOSE (Italian acronym for MOdulo Sperimentale Elettromeccanico) and by constructed esthetic landscapes with little impact on the environment, according to the community and local institutions [103].…”
Section: Mobile Damsmentioning
confidence: 99%
“…In Italy, the increasing frequency of coastal floods has been driven by an average sea level rise of 47 cm over the past 150 years [101], and sinking of the coast by natural and anthropogenic subsidence [102]. In Venice, the Italian coastal city most prone to flooding, the impacts of sea level rise are managed by mobile infrastructure called MOSE (Italian acronym for MOdulo Sperimentale Elettromeccanico) and by constructed esthetic landscapes with little impact on the environment, according to the community and local institutions [103].…”
Section: Mobile Damsmentioning
confidence: 99%
“…The timely combination of wind setup from strong south easterly Sirocco winds (Figure 2A), an inverted barometer effect due to the storm's low atmospheric pressure, high tides, and anomalously high mean sea levels in the Adriatic Sea (Figure 2B) resulted in this exceptional high-water level in Venice (Figure 2C). Several Adriatic Sea or more local forecasting systems are operated for the Venice region (e.g., Umgiesser et al, 2020), some of them using CMEMS forcing conditions. The CMEMS MedFS system forecasted high water levels, although with an underestimate of the peak of the event on November 12th (Figure 2D) (a feature common to all operational forecasting systems for Venice for this event, due to errors in atmospheric conditions forecasts).…”
Section: Forecasts and Hindcasts Of Sea Levelmentioning
confidence: 99%
“…An overview of the current European capacity in terms of operational modeling of marine and coastal systems was recently presented in Capet et al (2020) and indicated that about half of the reported regional / local ocean modeling systems rely on CMEMS models for open boundary conditions. A review of storm surge modeling for Europe is provided in Umgiesser et al (2020), with several systems also part of CMEMS or using CMEMS as boundary conditions. Recently, the OPENCoastS service has been developed to generate on-demand coastal ocean forecasts (Oliveira et al, 2020).…”
Section: Downscaling Copernicus Forecastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it can even be envisioned to downscale the AdriSC climate results during extreme events to a 1.5-km resolution in the atmosphere and up to 10 m (with an unstructured grid) along the coastal areas in the ocean, following the setup of some operational models in the Adriatic (e.g. for coastal floods, Umgiesser et al, 2020).…”
Section: Summary and Perspectivesmentioning
confidence: 99%